Analisis Konsentrasi Logam Berat pada Permukaan Tanah Berdasarkan Nilai Suseptibilitas Magnetik di Pesisir Teluk Lasolo dan Sekitarnya - Aziza Nur Aziza; Irawati Irawati; Erzam Salahudin Hasan (Program Studi Teknik Geofisika FITK UHO, 2023)
This research is located in Lasolo Bay, that is at Tapuemea Village, Molawe District, North Konawe Regency. The purpose of the study was to determine the concentration of heavy metals based on magnetic susceptibility values using X-Ray Fluorescence (XRF) and determine sediment quality. The results of XRF measurements showed that the highest concentrations of heavy metals for mining zones, coastal zones and residential zones were Nickel (Ni), Iron (Fe) and Cobalt (Co), while heavy metals that did not exceed the maximum threshold were Copper (Cu) and Zinc (Zn). Sediment quality as seen from the Pollution Load Index (PLI) analysis is included in the polluted category with a geoaccumulation index value indicating that there has been pollution with moderate to extremely severe pollution categories.